Sketching a Model on Fisheries Enforcement and Compliance -- A Survey - Coelho, M. P.; Filipe, J.; Ferreira, M. A. M. (arXiv:2306.16960, 2025)
Monitoring and enforcement considerations have been largely forgotten in the study of fishery management. This paper discusses this issue through a model formalization to show the impacts of costly, imperfect enforcement of law on the behavior of fishing firms and fisheries management. Theoretical analysis merges a standard bio-economic model of fisheries (Gordon-Schaefer) with Becker theory of Crime and Punishment.